Tibial Plateau Fracture Following Low Energy Fall in the Rocky Mountains - Arvanitakis, Alexandra V.; Mian, Kerry C.; Kreienkamp, Raymond; Rhoades, Charles E. (Kansas Journal of Medicine, 2019)
Tibial plateau fractures are debilitating injuries. They can occur in younger individuals who sustain a high energy trauma or, with increasing age, lesser degrees of trauma and underlying bone pathology such as osteoporosis, metabolic bone disease, and malignancy.1 Outside these cases, tibial plateau fractures are relatively uncommon. However, these fractures can occur in healthy patients who have sustained direct trauma to the knee. Fractures of the tibial plateau often are classified according to the Schatzker or AO classification systems.2,3 These systems evaluate the involvement of both the medial and lateral plateaus, degree of comminution, extension into the joint, and displacement (both articular surfaces and the relationship of the diaphysis to the metaphysis). Most tibial plateau fractures occur in the lateral aspect of the tibial plateau.1 The increased frequency of lateral fractures is due to the medial tibial plateau being able to resist higher weight-bearing load due to the presence of more cancellous bone. More importantly, the lateral plateau has more articular surface exposed during extension compared to the medial plateau, which increases likelihood of injury.4 The standard of care for most displaced tibial plateau fractures is surgical management with open reduction and internal fixation (ORIF).5 Conservative management, such as leg bracing, is an option for fractures that are nondisplaced or in patients too fragile for surgical intervention. In the senior population, a total knee arthroplasty (TKA) is a less common option. Tibial plateau fractures, particularly medial tibial plateau fractures, caused by direct trauma in the elderly, non-osteoporotic population are uncommon. We present the case of an active male without overt risk for severe fracture (10-year fracture risk of 10% via FRAX score) who was working to repair a trail in the Rocky Mountains. While other injuries were more likely given the mechanism of injury and patient risk, this case highlighted the importance of considering tibial plateau fracture, even in atypical settings without significant risk. Improved awareness of this mechanism of injury will lead to more accurate diagnosis and greater post-injury management.